Making Liberalism New : American Intellectuals, Modern Literature, and the Rewriting of a Political Tradition - Afflerbach, Ian, 1986- (Book collections on Project MUSE., 2021)
"This book maps the rise of a modern liberal culture in the United States from the 1930s to the 1960s. It shows how modern fiction writers responded to central concerns in liberal political thought, such as corporate ownership, reproductive rights, colorblind law, and presidential character"--